A política educacional do Paraná no período pandêmico 2020-2021 avaliada por pedagogas das escolas públicas estaduais - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The object of this research is Paraná’s educational policy, implemented by the Paraná State Department of Education (SEED-PR) in the 2020-2021 period. The aim of this study is to analyze Paraná's educational policy - the one that was developed in the context of the COVID- 19 pandemic (2020-2021). Such analysis is based on an evaluation performed by pedagogues who work at public schools in the state educational system. The specific objectives are: (a) to characterize the field and the agents of Paraná's educational policy implemented in the state public educational system in the 2020-2021 period, during the COVID-19 pandemic; (b) to reveal the school pedagogues' understanding about the political-educational guidelines imposed on public schools in the pandemic context; and (c) to indicate, based on the pedagogues' evaluation, the limits and possibilities evidenced in the educational offer in Paraná's state public schools during the pandemic period. The initial hypothesis was based on the idea that state public school pedagogues adapted and re-contextualized the state educational policy that was proposed during the 2020-2021 pandemic period. The main argument is based on the observation of the policies determined by SEED-PR and of the specific actions implemented within school institutions during the pandemic period, which make it possible, a priori, to reveal the vision of education and governance prevailing in the Paraná state government nowadays. The theoretical framework that substantiates the research is based on the evaluation of educational policies and programs (AFONSO, 2007; FERNANDES, 2010) and on Bourdieu's theory (1983; 1989) regarding the concepts of State, capital, field and porosity between fields, from a relational analysis approach, among others. The procedures used to produce the data were document analysis and an online questionnaire with open, closed and mixed questions, sent via Google Forms. The research participants were school pedagogues working at the Paraná Regional Education Centers (NREs). They were selected through intentional sampling. Moraes and Galiazzi's (2011) Textual Discourse Analysis (TDA) methodology was used to analyze the data collected. The results of the research revealed the intensification of the managerialist nature of state governance in Paraná, given the state's actions in the pandemic context. The data evaluated revealed some problematic aspects for school institutions, such as the distance between political and school agents, characterized by an authoritarian and bureaucratic relationship between them; the lack of consideration about school realities regarding the possibility of using technologies in the pandemic period; and the accumulation of bureaucratic work for school pedagogues. The results also indicate the relevance of the evaluation of Paraná's educational policy, carried out by the pedagogues who experienced it and re-contextualized it within the school field.
Keywords: Avaliação de Políticas e Programas Educacionais; Gerencialismo; Pandemia da COVID-19; Pedagogas; Política Educacional; Evaluation of Educational Policies and Programs; Managerialism; COVID-19 Pandemic; School Pedagogues; Educational Policy; CNPQ::CIENCIAS HUMANAS::EDUCACAO